2018
DOI: 10.1177/0263617418813018
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of long-term stable pullulan nanofibers via in situ cross-linking electrospinning

Abstract: Pullulan nanofibers with long-term stabilization were fabricated by using glutaraldehyde as the cross-linking agent and sulfuric acid as the catalyzer via in situ cross-linking electrospinning. The structural, chemical, and thermal analyses have been conducted by field emission scanning electron microscopy, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, and differential scanning calorimetry. Cross-linked pullulan nanofibers were found thermally more stable. More importantly, the wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…85 Because both PVA and HEC contain a large number of hydroxyl groups, the cross-linking reaction is mainly the aldol condensation. Similarly, the cross-linking reaction of e-spun nanofibers of individual dextran, 86 starch, 87,88 and PVA/starch mixture 89 is also dominated by aldol condensation. Another type of polysaccharide, CS, contains a large number of amino groups, which can undergo a Schiff base reaction with the aldehyde groups on GA.…”
Section: Classification and Mechanismmentioning
confidence: 99%
“…85 Because both PVA and HEC contain a large number of hydroxyl groups, the cross-linking reaction is mainly the aldol condensation. Similarly, the cross-linking reaction of e-spun nanofibers of individual dextran, 86 starch, 87,88 and PVA/starch mixture 89 is also dominated by aldol condensation. Another type of polysaccharide, CS, contains a large number of amino groups, which can undergo a Schiff base reaction with the aldehyde groups on GA.…”
Section: Classification and Mechanismmentioning
confidence: 99%
“…216 Similarly, recent work has shown that this method is valid also for polysaccharides. 217 Specifically, sulfuric acid was added to the formulation with glutaraldehyde to obtain in situ cross-linking of pullulan fibers. The cross-linking kinetic is even slower when glyoxal instead of glutaraldehyde is utilized as di-aldehyde cross-linker, similar to what was observed when reacting it with amines.…”
Section: Reactive Electrospinningmentioning
confidence: 99%
“…However, the output of traditional single-needle electrospinning technology is about 0.01-0.05 g/h, which greatly restricts its development and industrial applications. In order to solve the problem, much effort has been made, the focus was put on various needleless electrospinning technology [8][9][10][11], multinozzle electrospinning technology [12], bubble electrospinning [13,14], and macromolecular electrospinning [15][16][17].…”
Section: Introductionmentioning
confidence: 99%